Osmotic and Salt Stresses Modulate Spontaneous and Glutamate-Induced Action Potentials and Distinguish between Growth and Circumnutation in Helianthus annuus Seedlings - Stolarz, Maria; Dziubinska, Halina (Frontiers in Plant Science, 2017)
Action potentials (APs), i.e. long-distance electrical signals, and circumnutations (CN), i.e. endogenous plant organ movements, are shaped by ion fluxes and content in excitable and motor tissues. The appearance of APs and CN as well as growth parameters in seedlings and three-week old plants of Helianthus annuus treated with osmotic and salt stress (0-500 mOsm) were studied. Time-lapse photography and extracellular measurements of electrical potential changes were performed. The hypocotyl length was strongly reduced by the osmotic and salt stress. CN intensity declined due to the osmotic but not salt stress. The period of CN in mild salt stress was similar to the control (approx. 164 min) and increased to more than 200 min in osmotic stress. In sunflower seedlings growing in a hydroponic medium, spontaneous APs (SAPs) propagating basipetally and acropetally with a velocity of 12-20 cm min-1 were observed. The number of SAPs increased 2-3 times (7-10 SAPs 24h-1plant-1) in the mild salt stress (160 mOsm NaCl and KCl), compared to the control and strong salt stress (3-4 SAPs 24h-1plant-1 in the control and 300 mOsm KCl and NaCl). Glutamate-induced series of APs were inhibited in the strong salt stress-treated seedlings but not at the mild salt stress and osmotic stress. Additionally, in three-week old plants, the injection of the hypo- or hyperosmotic solution at the base of the sunflower stem evoked series of APs (3-24 APs) transmitted along the stem. It has been shown that osmotic and salt stresses modulate differently hypocotyl growth and CN and have an effect on spontaneous and evoked action potentials in sunflower seedlings. We suggested that potassium, sodium, and chloride ions at stress concentrations in the nutrient medium modulate sunflower excitability and CN.